De Gele Rijder : tentoonstellingen 1995. - Dekker, André; Dekkers, Geert; Geerlings, Harm; Heemstra, Han; Holtappels, Heiner; Kemper, Margriet; Otto, Peter; Paus, Jurgen; Ritmeester, Roland; Schnitzler, Peter; van Es, Martijn; van Meurs, Jacqueline; et al. (Arnhem : De Gele Rijder, 1996)
Lagendijk, Reinier ; Gerritsen, Hans ; Rikken, Miranda ; Traa, Jolande ; Krause, Anja ; Runge, Bianca ; Groot, David ; van Haarst, Sannetje ; van Vugt, Reinoud ; van Meurs, Jacqueline ; Roeten, René ; Oerlemans, Hester ; Hendriks, Maries ; Daudert, Nicole ; Yassievich, Tatyana ; Kraayer, Juul ; Zomer, Maya ; Dispa, Ada ; Hassink, Jacqueline ; Marcu, Georghe ; Batrinu, Iona ; Sarbulescu, Mihai ; van der Spek, Arjanne
Nederlands
boek